A new-historicist reading of Raymond Carver's representation of the working class and masculinity - Shariati-Rad, Saman (2014)
At first glance, Raymond Carver's short stories appear to be preoccupied with personal themes and inside-family relations rather than larger sociocultural issues; however, a closer examination reveals them to be interconnected with the broader narratives of American identity in the second half of the twentieth century. This study seeks to shed light on the mutually constitutive relationship between Carver's fiction on the one hand and the social, cultural, and political movements of his time on the other. Its whole process is premised on the New-Historicist idea that a work of literature not only is molded by the historical discourses of its era, but also is able to fashion its surrounding society. Based on this central principle, any interpretation of a literary text would be incomplete if the critic does not consider the text's association with the group of discourses which have helped shape it and to which the text, in its own turn, has been a forming response. Adopting such a New-Historicist perspective, my dissertation close reads twelve short stories by Raymond Carver along with their surrounding historical "co-texts." In one phase called "historicizing literature," I analyze the moments of progress and regress of 1970s and 1980s America to arrive at a heightened understanding of Carver's fiction. Then, in a second phase named "textualizing history," I examine Carver's work to better comprehend the society and culture within which it was produced and received. To evaluate the relationship between Carver's short stories and their historical positioning, my dissertation selects the two issues of "class" and "gender" as its main lenses of survey. However, since these two components of social identity cover vast areas, I pare them down to the subjects of the "working class" and "masculinity" to be able to respond to more focused questions. It must be noted that in Carver's fiction these two topics are related, as the author's depictions of the working class mostly revolve around the lives of some male characters. As my first objective in this thesis, I identify those working class and masculinity discourses of the American 1970s and 1980s which actively participated in shaping Carver's short stories. This investigation finally reveals the ways in which Carver's literary production was co-opted to serve the construction of social and political power in the Unites States. Then as a second objective, I determine the dissident discourses of the working class and masculinity injected by Carver's 1970s and 1980s short stories into the sociocultural arenas of the era. By analyzing how actively Carver's fiction participated in making cultural meanings and values, this section of my study unlocks the secret power of the literary text. It also shows how Carver helped to correct and improve the too often static and ideologically motivated portrayals of America's working-class masculinity. Lastly, following my third objective, I delineate Carver's typical image of the "working-class man" of 1970s and 1980s America. This last part of my research is the proof of the author's ability in making the narratives of working-class men in the United States more sympathetic, relatable, realistic, and humane.